Blockchain based integrity assurance framework for COVID‐19 information management & decision making at National Command Operation Center, Pakistan. (24th January 2023) - Zaid, Muhammad; Akram, Muhammad Waheed; Rizvi, Amna; Rizvi, Syed Khurram Jah
Summary: The uncontrollable spread of contagious disease COVID‐19 is a perennial threat to mankind and has resulted in an unprecedented lockdowns in several countries including Pakistan which in turn has caused an adverse socio‐economic impact to all industries. The strategic leadership and concerned state authorities are trying hard to combat and control the spread of COVID‐19 pandemic. The effective use of Information Management & Decision Support (IMDS) System can play significant role in combating pandemic and its spread, managing relief actions effectively, accessing vulnerable communities to roll out targeted subsidies by ensuring the coordinated effort and subsequent implementation. Reliable information is significantly critical to assist government and public health agencies in determining the best way forward to control this global health emergency. Therefore, this paper aims to strengthen capacity of IMDS System used by government institutions and authorities for decision making and information dissemination. In this research work, we addressed the integrity‐based issues that include completeness, correctness, and freshness of data by proposing a block chain‐based integrity protection mechanism. The proposed novel framework is a cascaded formulation of Integrity Assurance (IA) Protocol, Cryptographic Merkle Hash Tree, Digital Signature, and Blockchain. Beside cascaded formulation, two (2) schemes for MHT Generation are also presented in the framework. The proposed framework ensures fairness, completeness, and correctness of data that will be very helpful for secure data management, integration, and utilization in analysis for decision‐making. The proposed framework achieved an accuracy of more than 98.09% with better quantitative performance in standard evaluation parameters.